Mechanism study on pH-responsive cyclodextrin capped mesoporous silica: effect of different stalk densities and the type of cyclodextrin. (1st April 2015) - Bai, Ling; Zhao, Qinfu; Wang, Jian; Gao, Yikun; Sha, Zhou; Di, Donghua; Han, Ning; Wang, Ying; Zhang, Jinghai; Wang, Siling
Abstract: Cyclodextrin (CD)-capped mesoporous silica nanoparticles (MSN) with pH-responsive properties were synthesized, but little research has been carried out to evaluate the impact of critical factors such as the stalk density and the type of CD on the pH-responsive release behavior. Here, the effect of different stalk densities on the pH-responsive release behavior was investigated. Either too low or too high density of the grafted p-anisidine stalk could result in poor cargo release, and the optimum stalk density for MSN was measured by thermal analysis, and found to be approximately 8.7 stalks nm −2 . To achieve effective release control, the CD capes, α -CD and β -CD, were also investigated. Isothermal titration calorimetry (ITC) analysis was employed to determine the formation constants ( K f ) of the two CD with p-anisidine at different pH values. The results obtained showed that the complex of β -CD with p-anisidine had excellent pH-responsive behavior as it exhibited the largest changed formation constant ( ΔK f ) in different pH media. Furthermore, the pH-responsive mechanism between CD and p-anisidine molecules was investigated through ITC and a molecular modeling study. The release of antitumor drug DOX presents a significant prospect toward the development of pH-responsive nanoparticles as a drug delivery vehicle.